Mode Selection of a Relativistic Cherenkov Generator Based on Coaxial Combined Periodic Double-Corrugation Slow-Wave Structure - Ying Li; Jinchuan Ju; Ting Shu; Wei Zhang; Yunxiao Zhou; Hongtao Yao (IEEE Access)
The mode selection of a low guiding magnetic field relativistic Cherenkov generator based on coaxial combined periodic double-corrugation slow-wave structure (CPD-SWS) is studied. Owing to the flexible combination of different double-corrugation periods of the CPD-SWS, the electric field distribution can be modified and the coupling impedance of the specific mode can be enhanced, and thus the expected mode can be selected. The research results indicate that the quasi-TEM mode can be selected by adjusting the depth of the outer and inner corrugations of CPD-SWS. Moreover, the TM01 mode can be selected by adjusting the length of the corrugation and the depth of the outer corrugations of CPD-SWS. Furthermore, the TM02 mode can be selected by adjusting the depth of the outer corrugations and increasing the blade thickness. In addition, the particle in cell (PIC) simulation results show that the output microwave spectrum is pure for each case, which demonstrates that the quasi-TEM mode, TM01 mode and TM02 mode was selected successfully by using the CPD-SWS, respectively.